PENGARUH PERPUTARAN PERSEDIAAN BARANG TERHADAP LABA USAHA SWALAYAN BERSKALA BESAR DI KOTA BANDA ACEH - Jen Surya (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2009)
The aimed of research are to measure return on investment at big scale supermarket in Banda Aceh. The research do for Banda Aceh Industrial and Trading Agency registered supermarket, using selected criteria such as financial report, have trading capital up to 500 millions, have advantage and do purchasing 2 times in month. Based on 30 supermarket in Banda Aceh who fulfill the criteria, received 4 supermarket sample in this project. Analyze technical data using in this project are simple linear regression: Y=α+βX+ε elaborate with statistical analyze using statistical program for social science (SPSS). Data in this research use data from 2008 data compile with several financial report by 4 supermarket sample. Analyze from research with SPSS showing return on investment in the big scale supermarket result with the formula Y=35,250 +0, 95 X with Y are advantage and X are return on supplies, with hypothetical t count t table (4,4033,182). From this test showed return on investment have positive influence and significant to earnings of big scale supermarket in Banda Aceh. Independent Variable influence with dependent variable are 90, 6% and 9, 4% influence by other variable out of research. Keyword : return on investment, earnings